Novel Bioactive Glass-Modified Hybrid Composite Resin: Mechanical Properties, Biocompatibility, and Antibacterial and Remineralizing Activity - Han, Xiao; Chen, Yan; Jiang, Qian; Liu, Xin; Chen, Yaming (Frontiers in Bioengineering and Biotechnology, 2021)
Secondary caries seriously limits the lifetime of composite resin. However, integrating all desirable properties (i.e., mechanical, antibacterial, bioactivity, and biocompatibility) into one composite resin is still challenging. Herein, a novel bioactive glass (BAG)-modified hybrid composite resin has been successfully developed to simultaneously achieve excellent mechanical properties, good biocompatibility, and antibacterial and remineralizing capabilities. When the mass fractions of BAG particles were added from 8 to 23 wt %, the original mechanical properties of the composite resin, including flexural strength and compressive strength, were not obviously affected without compromising the degree of conversion. Although the BAG incorporation of mass fractions of 16 wt % to 23 wt % in composite resins reduced cell viability, the viability could be recovered to normal by adjusting the pH value. Moreover, the BAG-modified composite resins that were obtained showed good antibacterial effects against Streptococcus mutans and enhanced remineralizing activity on demineralized dentin surfaces with increasing incorporation of BAG particles. The possible mechanisms for antibacterial and remineralizing activity might be closely related to the release of bioactive ions (Ca2+, Si4+), suggesting that its antibacterial and biological properties can be controlled by modulating the amounts of bioactive ions. The capability to balance the mechanical properties, cytotoxicity, antibacterial activity, and bioactivity makes the BAG-modified composite resin a promising prospect for clinical application. Our findings provide insight into better design and intelligent fabrication of bioactive composite resins.